Orthographic Contamination of Broca’s Area - Montant, Marie; Schön, Daniele; Anton, Jean-Luc; Ziegler, Johannes C. (Frontiers in Psychology, 2011)
Strong evidence has accumulated over the past years suggesting that orthography plays a role in spoken language processing. It is still unclear, however, whether the influence of orthography on spoken language results from a co-activation of posterior brain areas dedicated to low-level orthographic processing or whether it results from orthographic restructuring of phonological representations located in the anterior perisylvian speech network itself. To test these hypotheses, we ran a fMRI study that tapped orthographic processing in the visual and auditory modalities. As a marker for orthographic processing, we used the orthographic decision task in the visual modality and the orthographic consistency effect in the auditory modality. Results showed no specific orthographic activation neither for the visual nor the auditory modality in left posterior occipito-temporal brain areas that are thought to host the visual word form system. In contrast, specific orthographic activation was found both for the visual and auditory modalities at anterior sites belonging to the perisylvian region: the left dorsal-anterior insula and the left IFG. These results are in favor of the restructuring hypothesis according to which learning to read acts like a “virus” that permanently contaminates the spoken language system.